Mucilage extracted from Chilean papaya seeds is enriched with homogalacturonan domains - Sanhueza, Dayan; Sepúlveda-Orellana, Pablo; Salazar-Carrasco, Alejandra; Zúñiga, Sebastian; Herrera, Raúl; Moya-León, María Alejandra; Saez-Aguayo, Susana (Frontiers in Plant Science, 2024)
Chilean papaya, also known as mountain papaya (Vasconcellea pubescens), is a local fruit in Chile, recognized for its rich papain content, fruity fragrance, and nutritional value. The oblong fruit has five distinct ridges and a seed-filled cavity embedded in mucilage. Typically consumed cooked due to its high protease content, the mucilage, usually discarded, is a readily available byproduct. This study analyzed the biochemical composition of mountain papaya mucilage, revealing that papaya seeds yield nearly 20% of their weight in mucilage polysaccharides. The mucilage, separated into soluble and adherent layers, exhibited a high proportion of acidic sugars. Biochemical analysis highlighted the prevalence of galacturonic acid, indicating a significant homogalacturonan (HG) domain. The HG-rich mucilage, currently discarded as waste, emerges as a promising source for polysaccharides, particularly HG, with potential applications in health and the food industry. The mucilage also contains other pectin domains, suggesting its multifaceted utility in various industrial applications.